Manejo del dolor abdominal en usuarios que acuden al servicio de emergencia del Hospital Básico Catacocha. - Godoy Armijos, Daniel José (2016)
The abdominal pain is one of the most frequently symptoms by which patients often go to the Emergency Department, constituting almost 85% of emergency care. According to the National Institute of Statistics and Censuses of Ecuador, in 2011, the abdominal pain was one of the 10 causes of morbidity in the country. The Panamerican Health Organization, 2011, defines abdominal pain as the most important manifestation of most of the disorders. The main objective of the present study is to know the handling of the abdominal pain in users who visit the Emergency Service of the Catacocha Basic Hospital in the period of March to July 2016; and the specific objectives are: 1. To determine which kind of analgesia is the most frequently used in the handling of abdominal pain in users who visit the emergency; 2. To determine which were the most frequent pathologies found in users who presented abdominal pain in emergency; 3. To determine the handling of surgical abdominal pain in emergency users. This investigation carries out a descriptive, quantitative, retrospective study, employing 500 patients with abdominal pain; obtaining a sample of 64 patients who meet the inclusion and exclusion criteria; A data collection report was prepared by the author; Obtaining the following results; 44% were treated with tramadol; 3% antispasmodic; 42% The most frequent cause of abdominal pain was appendicitis; 11% mesenteric adenitis. The management of acute abdominal pain in patients diagnosed with appendicitis was: 15 patients with tramadol; 5 patients with ketorolac; While those diagnosed for cholecystitis were managed: 5 patients with tramadol; 5 patients with ketorolac. The most frequent analgesic used in the treatment of abdominal pain at the Catacocha Basic Hospital was tramal with 44%, ketorolac with 42%, and antispasmodics with 6%. Key words: Abdominal pain, Laparotomy, Appendectomy, Appendicitis.